Modifiable factors of development and recurrence of adenomatous colorectal polyps (literature review) - I. G. Gataullin; B. A. Sakhabetdinov; B. R. Valitov; K. N. Ermakova; A. V. Kalyamova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Adenomatous colorectal polyps are associated with a high risk of developing a malignant tumor. They are considered precancerous conditions and can lead to the development of colorectal cancer. To date, colorectal cancer ranks third in the world in frequency of occurrence among all malignant neoplasms.Objective. Improving the results of diagnosis and surgical treatment of patients with colorectal adenomatous neoplasms by identifying development factors and identifying risk groups for this nosology.Materials and methods. Analysis of literary data.Results. Among the factors leading to the development of colorectal polyps, it is worth noting a genetic predisposition, so by immunoblotting, PCR sequencing of the entire exome in cases of patients with familial dentate polyposis, rare variants of the germ line in the WNK2 gene were identified. Functional studies have shown that variants of the WINK2 germ line affect protein function in the context of the MAPK pathway, a molecular trait of this disease. Also, in the course of many domestic and foreign randomized clinical trials, the following modifiable factors for the development of adenomatous colorectal polyps were identified.Conclusion. The study revealed the factors of development and recurrence of colorectal neoplasms and identified risk groups for this nosology. The study revealed low compliance of patients with respect to changes in certain living conditions (the use of ethyl alcohol and products containing it, tobacco smoking, both active and passive, the fight against obesity and inactivity), which leads to recurrence and increases the risks of malignancy of colorectal polyps.